International construction arbitration law - Jenkins, Jane (Arbitration in context series, 2021)
International Construction Arbitration Law', the eminent practical guide in this third edition, is aimed at addressing the significant developments in the practice of dispute resolution on major construction and engineering projects. The text, updated to include the latest edition of arbitral rules and to introduce the Prague Rules, considers the full range of available dispute resolution methods, including mediation, conciliation and determination by dispute review boards, before focusing specifically on arbitration. The third edition addresses fresh thinking on MedArb, guidance on preparation for and conduct of virtual hearings in the wake of COVID-19, technological advances to assist collection and presentation of evidence, litigation funding and includes a new chapter on the role of arbitration in tender disputes.